HDAC3 inhibition ameliorates spinal cord injury by immunomodulation - Tomoharu Kuboyama (Nature Portfolio, 2017)
Abstract Following spinal cord injury (SCI), the innate immune response of microglia and infiltrating macrophages clears up cellular debris and promotes tissue repair, but it also inflicts secondary injury from inflammatory responses. Immunomodulation aimed at maximizing the beneficial effects while minimizing the detrimental roles of the innate immunity may aid functional recovery after SCI. However, intracellular drivers of global reprogramming of the inflammatory gene networks in the innate immune cells are poorly understood. Here we show that SCI resulted in an upregulation of histone deacetylase 3 (HDAC3) in the innate immune cells at the injury site. Remarkably, blocking HDAC3 with a selective small molecule inhibitor shifted microglia/macrophage responses towards inflammatory suppression, resulting in neuroprotective phenotypes and improved functional recovery in SCI model. Mechanistically, HDAC3 activity is largely responsible for histone deacetylation and inflammatory responses of primary microglia to classic inflammatory stimuli. Our results reveal a novel function of HDAC3 inhibitor in promoting functional recovery after SCI by dampening inflammatory cytokines, thus pointing towards a new direction of immunomodulation for SCI repair.